Asymmetric Supercapacitors Based on Hierarchically Nanoporous Carbon and ZnCo2O4 From a Single Biometallic Metal-Organic Frameworks (Zn/Co-MOF) - He, Da; Gao, Yu; Yao, Yucen; Wu, Ling; Zhang, Jiang; Huang, Zheng-Hong; Wang, Ming-Xi (Frontiers in Chemistry, 2020)
Metal-organic frameworks (MOFs) have triggered numerous interests in supercapacitos (SCs) due to their large specific surface area and tunable pore structure, but their poor electrochemical conductivity and ion insertion steric hindrance limit their use as high-performance electrodes of supercapacitors. Bimetallic MOFs could provide rich redox reactions deriving from improved charge transfer between different metal ions, so their supercapacitor performance can be enhanced greatly. In this study, “One-for-All” strategy is adopted to synthesize both positive and negative electrodes for hybrid asymmetric SCs (ASCs) from a single bimetallic MOF. Bimetallic Zn/Co-MOF with cuboid-like structures were synthesized by a simple method, the MOF-derived nanoporous carbons (NPC) and bimetallic oxides (ZnCo 2 O 4 ) were obtained by post heat treatment and rinsing with HCl. The as-prepared MOF derived NPC and bimetallic oxides were utilized as negative and positive materials to assemble hybrid ASCs with 6 M KOH as electrolyte. Thanks to the matchable voltage window and specific capacitance between the negative (NPC) and positive (ZnCo 2 O 4 ), the as-assembled ASCs deliver high specific capacitance of 94.4 F/g (cell), excellent energy density of 28.6 Wh/kg at a power density of 100 W/kg, and high cycling stability of 87.2% after 5000 charge-discharge cycles. This strategy is promising in producing high-energy-density electrode materilas in supercapacitors.